(untitled) (Academicia Globe: Inderscience Research, 2021)
In the modern scientific system of Uzbekistan, the establishment of a pedagogical process related to the joint education and upbringing of healthy children and children with disabilities is becoming one of the urgent tasks of the new educational process. In Uzbekistan, special education has been developed as a system of education for children with disabilities. This teaching is based on the assumption that the needs of children with disabilities cannot be met in general education institutions. Special education operates worldwide in the form of schools or boarding schools, as well as small parts of secondary schools.